Profil Fitokomponen dan Aktivitas Ekstrak Metanol Daun Intaran Bali (Azadiractha indica Juss.) terhadap Candida albicans ATCC-10231 - Meylana Ayu Melinda; Agung Nova Mahendra (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Candidiasis, usually caused by Candida albicans is commonly found in clinical settings. Resistance of C. albicans against antifungals is an emerging issue. This study was aimed to determine the selected quantitative phytocomponent profile and evaluate the effectiveness of intaran (Azadiractha indica A. Juss) leaf extract from Bali in inhibiting the growth of C. albicans .Methods: This experimental research was conducted at the Center for Marine Aquaculture Research and Development (Buleleng, Bali), Laboratory Service Unit, Faculty of Agricultural Technology, Udayana University, and Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Udayana University, Denpasar, Bali. Our study included the preparation of the methanol extract of intaran leaves using maceration method, phytochemical analysis, and testing the antifungal activity of the extract using the diffusion disk assay against C. albicans ATCC-10231.Results: Phytochemical components in the methanol extract of intaran Bali leaves were chlorophyll (18434.47 mg/L), total antioxidants (4818.07 mg/L GAEAC), phenol (4391.16 mg/100gr GAE) and flavonoids (785.32 mg/100gr QE). The extract exhibited dose-dependent effect, with greatest inhibition against C. albicans ATCC-10231 growth was obtained at the concentration of 50%.Conclusion: Methanol extract of Balinese intaran leaves contained significant amount of chlorophyll, total antioxidants, phenol, and flavonoids. The extract showed antifungal activity against C. albicans ATCC-10231. This anticandidal effect is assumed to be related to the phytocomponents of the extract.